Optimization of product mix in a typical yarn manufacturing industry - Hasan, S. Mainul; Karim, A.N. Mustafizul (Department of Mechanical Engineering, BUET, Dhaka, 2003)
In a typical yam manufacturing company different types of yams are produced and usually a schedule of production is prepared and followed for smoother production. However, company's taking decision regarding order receiving and scheduling become tougher when it gets simultaneous orders of different yams. A compromise is required between profit and capacity. An LP model has been formulated for some selected yams and solved and this paper presents an analysis to find the optimum product mix indicating the quantity (tons) of each category of yams to be produced and the duration of machine hours to be allocated. It would also help to identify the abundant or scarce resources. Moreover, through the analysis it is possible to prioritize the expansion of the scarce resources in allocation of additional investment, if required. A sensitivity analysis in this regard provides the information of increment of the scarce resources and maximum change in marginal profit